2015
DOI: 10.1145/2677087
|View full text |Cite
|
Sign up to set email alerts
|

From Scratch to “Real” Programming

Abstract: Computer science (CS) activities for young students are widely used, particularly visual programming environments. We investigated the use of the Scratch environment for teaching CS concepts to middle school students. In a previous article [Meerbaum-Salant et al. 2013], we reported on the extent to which the CS concepts were successfully learned. In this article, we look at the transition from studying CS with the visual Scratch environment in middle school to studying CS with a professional textual programmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(98 citation statements)
references
References 19 publications
2
75
1
10
Order By: Relevance
“…In a study of 10th graders learning C# or Java [1], those who had taken a Scratch course in 9th grade learned more quickly, understood loops better, and were more engaged and confident than their peers who had not. However, in the final test, a significant difference was seen in only one of three cognitive dimensions.…”
Section: Measuring Learning Transfermentioning
confidence: 99%
“…In a study of 10th graders learning C# or Java [1], those who had taken a Scratch course in 9th grade learned more quickly, understood loops better, and were more engaged and confident than their peers who had not. However, in the final test, a significant difference was seen in only one of three cognitive dimensions.…”
Section: Measuring Learning Transfermentioning
confidence: 99%
“…In existing work, we can see many examples of blocks programming being used as an effective approach for teaching computer science concepts to students of all ages within formal education settings [6], [7]. Through representing programmatic constructs as coloured jigsaw-puzzle pieces, this lowers the barriers imposed by textual programming languages such as Java or C++ that are used as introductory languages for novices.…”
Section: The Solution -Blocks?mentioning
confidence: 99%
“…Armoni et al [2] looked at the effect of having previously learnt Scratch on the learning of text-based programming. Their results indicated a slight improvement in performance, but also suggested that students with exposure to Scratch were better motivated and learnt more quickly.…”
Section: Transition From Blocks To Textmentioning
confidence: 99%